Mapping the Tourism Potential of Linggamekar Village, Cilimus District, Kuningan Regency, West Java - Gantina, Devita; Nurmalinda, Elda; Rianto (Technium Social Sciences Journal, 2025)
This study aims to map the tourism potential of Linggamekar Village, located in the Cilimus District of Kuningan Regency, West Java. As a rural area with rich natural and cultural assets, Linggamekar possesses significant opportunities for tourism development, particularly within the context of community-based and sustainable tourism. The research identifies and categorizes the village’s tourism potential across several dimensions, including natural attractions, cultural heritage, local traditions, creative industries, and supporting facilities. Using a qualitative descriptive method, data was collected through field observations, interviews with local stakeholders, and a review of village documents. The findings indicate that Linggamekar Village offers diverse tourism resources, such as its scenic agricultural landscapes, community craftsmanship, and cultural performances supported by strong social cohesion. The village also demonstrates readiness for tourism development through active community participation and existing micro-scale tourism initiatives. However, several challenges remain, including limited destination infrastructure, low promotional visibility, and the need for capacity building among local tourism actors. Strengthening collaboration between the local government, educational institutions, and community organizations is essential to transform Linggamekar into a competitive rural tourism destination. This study provides strategic insights to support future tourism planning and sustainable development in the village.